2009
DOI: 10.1038/bmt.2009.97
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac complications in patients undergoing a reduced-intensity conditioning hematopoietic stem cell transplantation

Abstract: Reduced-intensity conditioning (RIC) extends hematopoietic stem cell transplants (HSCT) to elderly or debilitated patients who are not candidates for HSCT. The incidence and outcomes of cardiac complications have been reported following myeloablative HSCT. We assessed the incidence and outcomes of cardiac complications in 278 recipients of RIC from July 2000 to July 2006. All patients received conditioning with BU, fludarabine and TBI. Patients were evaluated from conditioning therapy until 100 days after HSCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 31 publications
1
31
0
3
Order By: Relevance
“…The median time of onset of arrhythmias was 9 days after AHCT and this is slightly later than the onset of between 3–7 days as reported by earlier studies [6, 8, 9]. Most arrhythmias were however short lasting with median duration of less than a day.…”
Section: Discussionsupporting
confidence: 51%
“…The median time of onset of arrhythmias was 9 days after AHCT and this is slightly later than the onset of between 3–7 days as reported by earlier studies [6, 8, 9]. Most arrhythmias were however short lasting with median duration of less than a day.…”
Section: Discussionsupporting
confidence: 51%
“…Our findings that patients with an elevated creatinine level, prior mediastinal radiation or a history of previous arrhythmia were more likely to develop AF/ AFL, have not been described previously as potential risk factors for the development of AF/AFL in the post auto-HSCT period. [8][9][10] In our study, development of AF/AFL was not associated with a longer hospital stay, or inferior survival at 100 days. In contrast, Hidalgo et al, whose study included both allogeneic and autologous HSCT, found that development of AF/AFL prolonged hospitalization and predicted for higher 30-day mortality.…”
Section: Discussionmentioning
confidence: 64%
“…It was proved that stem cells improve patients' survival and quality of life [6]. However, several other studies have shown a chance of complications and adverse side effects at SCs transplantation [7][8][9]. These differences are explained by the use of SCs from various sources and, consequently, with different properties.…”
mentioning
confidence: 91%
“…The cell preparation include of immature committed hematopoietic progenitors and mature blood cells. The number of nucleated cells in the samples ranged from 0.89·10 9 to 0.95·10 9 , the number of mononuclear cells -from 0.486·10 9 to 0.520·10 9 , CD34…”
mentioning
confidence: 99%